TiO2 synthesized by microwave assisted solvothermal method: Experimental and theoretical evaluation - Moura, K. F.; Maul, J.; Albuquerque, A. R.; Casali, G. P.; Longo, E.; Keyson, D.; Souza, A. G.; Sambrano, Julio Ricardo [UNESP]; Santos, I. M. G. (Elsevier B.V., 2014)
In this study, a microwave assisted solvothermal method was used to synthesize TiO2 with anatase structure. The synthesis was done using Ti (IV) isopropoxide and ethanol without templates or alkalinizing agents. Changes in structural features were observed with increasing time of synthesis and evaluated using periodic quantum chemical calculations. The anatase phase was obtained after only 1 min of reaction besides a small amount of brookite phase. Experimental Raman spectra are in accordance with the theoretical one. Micrometric spheres constituted by nanometric particles were obtained for synthesis from 1 to 30 min, while spheres and sticks were observed after 60 min. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: TiO2; Nanoparticles; Microwave solvothermal synthesis; Computational periodic model; B3LYP-D*